THE INFLUENCE OF TANNERY EFFLUENT ON BIOCHEMICAL CONSTITUENTS IN THE TISSUES OF OREOCHROMIS MOSSAMBICUS - A.PARITHA BHANU; K.J.KHUSNUMA BEGAM; M.DEEPAK (International Journal of Pharma and Bio Sciences, 2014)
Bioassays were carried out to find out LC50 96 hr value of the tannery effluent on the freshwater teleost fish O.mossambicus and it was found to be 15%. The effluent was found to bring alterations in various biochemical constituents in tissues like gills, liver and intestine of the fishes. There was a significant increase in the concentrations of the total free amino acids in all the tissues of 0.mossambicus, whereas overall decrease in the total protein, free sugars and total proteins in gills, liver and intestine. The decrement of proteins, free sugars and lipids could be due to utilization of these as an energy source under the condition of emergency during prolonged stress. Thus the tannery effluent caused alterations in the fundamental biochemical mechanism in the present experimental animal leading to mortality in them.